Effects of Tillage Systems and Bacterial Inoculation on Enzyme Activities and Selected Soil Chemical Properties - Ana Ursu; Irina Gabriela Cara; Geanina Bireescu; Mariana Rusu; Gabriel Dumitru Mihu; Segla Serginho Cakpo; Denis Țopa; Gerard Jităreanu (Agriculture)
Excessive tillage and chemical fertilization are the primary attributes of conventional farming and the main causes of soil degradation. This research focused on the comparative study of two tillage systems: conventional (CT) and no-tillage (NT), as well as on the effect of chemical fertilizers and different Bacillus megaterium var. phosphaticum inoculum rates (75, 100 and 125%) on soil properties. This short-term experiment was conducted under field conditions in Northeastern Romania from 2023 to 2024. Soil dehydrogenase, catalase, acid, and alkaline phosphatase activities, pH, organic carbon content (SOC), total nitrogen (TN), total phosphorus, and available phosphorus (TP and AP) were determined. Bacillus treatments generally inhibited soil enzyme activity by 0.35 to 57%, depending on the enzyme type. Under NT, activity increased by up to 59% for dehydrogenase, 43% for acid phosphatase, and 70% for alkaline phosphatase compared to the CT system. An opposite trend was found for catalase, along with a negative correlation with the other enzymes. There were positive differences in TP concentration at 125% Ecofertil + N in both CT (0.0577 ppm) and NT (0.0578 ppm) in 2023 compared to the control (0.0346–0.0374 ppm). In the same year, after the first inoculation, AP increased significantly with bacterial treatments in CT, from 32.34% (T0) to 47.94% (T4), and at crop harvest in NT in 2024, from 34.18% (T0) to 91.06% (T3). The results suggest that enzymatic activities and soil chemical properties were more influenced by soil management than the interaction between inoculated bacteria and chemical fertilizers.